Analisis Persistensi Penggunaan Obat Antihipertensi Terhadap Pencapaian Tekanan Darah Optimal pada Pasien di Puskesmas - Serli Andini; Nurmainah Nurmainah; Mohammad Andrie (Journal Syifa Sciences and Clinical Research, 2022)
Persistence of the use of antihypertensive drugs in hypertensive patients is very necessary considering the main outcome of hypertension therapy is to prevent cardiovascular disease events such as myocardial infarction and stroke which can lead to death. This study aims to analyze the relationship between characteristic factors and drug use factors with the persistence of antihypertensive drug use and to determine the average blood pressure of outpatient hypertension patients at Sungai Raya Dalam Public Health. This study uses a retrospective cohort study design and uses secondary data sources for outpatient hypertension patients at Sungai Raya Dalam Public Health Center, Kubu Raya Regency. Persistence measurement method is the gaps between refill method with a grace period of 14 days for taking the drug. Data were analyzed using chi square test. The number of subjects who took part in this study were 402 hypertensive patients who used antihypertensive drugs (diagnostic index date 1 June 2020 to 30 June 2021). The results showed that the majority of the characteristics of hypertensive patients who visited the Sungai Raya Dalam Public Health Center tended to be 45 years old (57.7%), female (58.7%), patients with monotherapy therapy regimens (73.9%), and patients with CCB therapy (66.9%). Only (36.3%) patients had persistent use of antihypertensive drugs. Chi square analysis showed that there was no significant relationship between age (p=0.715) and gender (p=0.786), statistically there was a statistically significant relationship between therapy regimen (p=0.000) and type of therapy (p=0.029). The conclusion from the research is that the persistence of drug use is influenced by the regimen and type of hypertension therapy.